Energy efficient communication based on self-organisation of IoT devices for material flow tracking. Issue 1 (2019) - Škulj, Gašper; Sluga, Alojzij; Bračun, Drago; Butala, Peter; Vrabič, Rok
Abstract: Material flow management is an increasingly difficult activity in today's ever-more-complex manufacturing systems. New approaches are offered by the industrial internet of things (IoT), which is envisioned as a network of active devices that are capable of wireless communication. However, the dependence of IoT devices on battery energy presents a maintenance challenge. The paper proposes a self-organisation-based approach to improve the overall energy efficiency of workpiece localisation using IoT devices. A simulation study is performed to show the effects of transmitter effectiveness, material flow dynamics, and system scale on the energy efficiency.